2015
DOI: 10.3892/ijo.2015.2823
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between in vitro drug sensitivity and clinical response of patients to treatment in chronic lymphocytic leukemia

Abstract: Abstract. to improve the efficacy of therapeutic options in chronic lymphocytic leukemia (cll) an in vitro system to determine the response of mononuclear blood cells from blood of patients was elaborated. the study combines four approaches, i.e., cell viability, apoptosis rate, differential scanning calorimetry (DSc), and immunoblotting to develop personalized therapy protocols based on the cell sensitivity to drug exposure of individual cll patients. the complementary analyses were performed on 28 peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 39 publications
(33 reference statements)
1
16
0
Order By: Relevance
“…A previous study of 28 patients with CLL (15), and a previously published case report (20), revealed a correlation between apoptosis induction potential of cells isolated from peripheral blood of untreated CLL patients to the subsequent application of anticancer drugs (cladribine, mafosfamide, fludarabine, rituximab or their combinations). The present study compared two blood analyses from a young previously-untreated adult female.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…A previous study of 28 patients with CLL (15), and a previously published case report (20), revealed a correlation between apoptosis induction potential of cells isolated from peripheral blood of untreated CLL patients to the subsequent application of anticancer drugs (cladribine, mafosfamide, fludarabine, rituximab or their combinations). The present study compared two blood analyses from a young previously-untreated adult female.…”
Section: Introductionmentioning
confidence: 88%
“…The fractions of viable and apoptotic cells following 48 h of exposure were determined by Vybrant Apoptosis assay kit #4 (Molecular Probes; Thermo Fisher Scientific, Inc., Waltham, MA, USA), as described previously (15). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations